The Contribution of Islamic Education to Social and Cultural Development in Society - Hoktaviandri, Hoktaviandri; Mislaini, Mislaini; Akmal, Fauzi; Yanti, Novia (Al-kayyis: Journal of Islamic Education, 2025)
Islamic education plays a very strategic role in various aspects of social life, especially in strengthening spirituality, shaping noble character, developing a culture rooted in Islamic values, and strengthening social and cultural cohesion in community life. This article comprehensively and thoroughly discusses how Islamic education is able to adapt and respond to social developments in society, as well as its role and contribution in preserving, supporting, and strengthening local cultural resilience. In this case, Islamic education is expected to be able to internalize Islamic values into the daily lives of society, thereby creating a more moral, inclusive, and characterful social order. This article was written using the qualitative method with content analysis. Data sources were taken from books, journals, and other sources. All data were analyzed using the Miles and Huberman thematic technique. The results of the analysis show that Islamic education makes a real contribution in various aspects of life, including through the instillation of moral values.